2017
DOI: 10.1063/1.4997562
|View full text |Cite
|
Sign up to set email alerts
|

Increased electrical conductivity of peptides through annealing process

Abstract: Biocompatible biologically occurring polymer is suggested as a component of human implantable devices since conventional inorganic materials are apt to trigger inflammation and toxicity problem within human body. Peptides consisting of aromatic amino acid, tyrosine, are chosen, and enhancement on electrical conductivity is studied. Annealing process gives rise to the decrease on resistivity of the peptide films and the growth of the carrier concentration is a plausible reason for such a decrease on resistivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The here observed increases in the conductivity cannot be ascribed to the formation of films akin to dense carbon black materials (Celzard et al, 2002; Jan et al, 2006), because the processes producing these materials operate high temperatures (1,000°C or more) when applied to eumelanin-like materials (Kong et al, 2012; Li et al, 2013), or anyway at temperatures above 600°C to obtain good conductivity values when applied to polypeptides rich in eumelanin precursors (phenylalanine) (Namgung et al, 2017). Instead, in this study it is observed a notably conductivity increase, from 3 to 5 orders of magnitude, even after annealing in the 200°C÷450°C range.…”
Section: Resultsmentioning
confidence: 99%
“…The here observed increases in the conductivity cannot be ascribed to the formation of films akin to dense carbon black materials (Celzard et al, 2002; Jan et al, 2006), because the processes producing these materials operate high temperatures (1,000°C or more) when applied to eumelanin-like materials (Kong et al, 2012; Li et al, 2013), or anyway at temperatures above 600°C to obtain good conductivity values when applied to polypeptides rich in eumelanin precursors (phenylalanine) (Namgung et al, 2017). Instead, in this study it is observed a notably conductivity increase, from 3 to 5 orders of magnitude, even after annealing in the 200°C÷450°C range.…”
Section: Resultsmentioning
confidence: 99%
“…21 Also, the specic peptide sequence used in this research can be formed into a large-area lm and its resistivity can easily be tuned. 22,23 Such exibility of the peptide sequence is expected to be helpful in future research, as the mechanical and electrical properties of the peptide can be altered in researcher's favor.…”
Section: Introductionmentioning
confidence: 99%
“…The optical bandgap was determined by extrapolating the linear region of the plot until it intersected with the x -axis. The method has been widely used to estimate bandgaps based on optical absorbance spectra [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%